Motherhood and breastfeeding after brest carcinoma - Valent, Dragana (General Practice, 2024)
Introduction. Breast cancer is the most prevalent cancerin women. The most reliable method to diagnose breastcancer is through mammography, combined with ultrasonographyor magnetic resonance imaging. The treatment planmay include surgery, radiation therapy, chemotherapy, hormonetherapy, targeted therapy, or immunotherapy.Case report. The following is a case report of a 46-yearoldwoman who visited a physician in 2007 when she wasplanning her second pregnancy. She was 30 years old at thetime. During a routine breast self-examination, she noticeda lump and was sent for an ultrasound examination wherethe tumor was confirmed. After diagnosis and preoperativepreparation, she underwent breast-preserving surgery of theleft breast, along with axilla dissection due to positive lymphnodes. Pathohistologic findings confirmed Carcinoma mixtuspraecipue ductale G2 et partim mucinosum G2, while nometastatic changes were found in the axillary lymph nodes.The tumor’s hormonal status was estrogen 1, progesterone 1,and HER2 2. The patient received six rounds of FAC chemotherapyfollowed by 16 rounds of trastuzumab. After startingon tamoxifen and using it until December 2009, she had toundergo the removal of her right ovary due to the discoveryof numerous cysts. Several cysts were also found on the leftovary. Five years after her breast cancer surgery, the patientbecame pregnant and gave birth to a baby girl. She breastfedher for ten months from the breast that was not operated on.Conclusion. Breast cancer is a serious illness that cangreatly affect the reproductive health of young women. It isessential to take into account the patient’s desire to have childrenafter treatment. Therefore, it is crucial to provide appropriatetherapy and counseling.
Keywords: pregnancy; chemiotherapy; hormone therapy; anti-HER2 therapy; ovary cyst